Ethanol Administration in Mice Leads to Sex-Specific Changes in the Acetylation of α-Tubulin in the Cerebellum - Abosede Elesinnla; Rehana Khatoon; Nicholas Kleinert; Junfang Wu; Jaylyn Waddell; Tibor Kristian (Brain Sciences)
Background: Acetylation of α-tubulin is an important post-translational modification that helps maintain microtubules’ stability and dynamics, including axonal transport, cell signaling, and overall neuronal integrity. This study investigates sex-based differences in alcohol-induced acetylation of α-tubulin in mouse cerebellum. Methods: Adult, 3-month-old male and female C57BL/6 mice were administered 20% ethanol intraperitoneally. The cerebellum was dissected at 30 min, 1 h, 2 h, and 4 h post-injection. Expression levels of cerebellar acetylation of α-tubulin and enzymes mediating acetylation/deacetylation were analyzed by Western blot. The downstream product of ethanol metabolism, acetyl-CoA, was quantified by HPLC. Results: In males, α-tubulin acetylation levels increased significantly as early as 30 min post-ethanol injection, whereas females exhibited increased acetylation at a later time point, after 1 h. These sex-specific changes coincided with alterations in acetyl-CoA levels that increased significantly at 15 min in males and 1 h in females following ethanol administration. Furthermore, the level of acetyltransferase that acetylates tubulin increased significantly at 30 min in males and 1 h in females. Notably, however, no significant changes were observed in the level of the tubulin deacetylating enzyme, HDAC6, in either sex. Conclusions: Our data demonstrate that these sex differences stem from variations in expression levels of tubulin acetyltransferase (αTAT1), and the rate of ethanol metabolism-related acetyl-CoA production between male and female animals.